The Active Compound Content of Jamblang (Syzygium cumini) as an Anti-Breast Cancer - Mindawati, Erisa; Depita Nurapni; Nurhalimah; Siti Solihat; Himyatul Hidayah (Eureka Herba Indonesia, 2024)
Jamblang is rich in bioactive compounds such as anthocyanins, phenolics, and flavonoids. Anthocyanins, which give jamblang fruit its dark color, have been known for their antioxidant properties that can fight oxidative stress, which is linked to the development of cancer. Phenolics, with their anti-inflammatory and antioxidant properties, provide additional protection to body cells. Flavonoids, with a wide range of biological activities, including anti-cancer properties, could potentially be promising agents in cancer prevention and treatment efforts. The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding the potential of the active compound Jamblang (Syzygium cumini) as anti-breast cancer. This study follows the preferred reporting items for systematic reviews and meta-analysis (PRISMA) recommendations. The jamblang plant has potential as an anti-breast cancer agent. Jamblang plants are rich in active compounds that have anticancer activity, namely anthocyanins, flavonoids, phenolic compounds and carotenoids. These compounds can inhibit cancer cell growth, trigger apoptosis, and inhibit metastasis.